IMPLEMENTASI SISTEM INFORMASI AKUNTANSI BERBASIS CLOUD PADA SIKLUS PENJUALAN UNTUK MENINGKATKAN EFEKTIVITAS PENGELOLAAN KEUANGAN PT X - Sariyanti; Triswastika, Arimbi; Mecca Sufyana, Candra (INFOKOM (Informatika & Komputer), 2025)
The development of cloud computing technology has created new opportunities for companies to improve the efficiency and effectiveness of information management, including in the field of accounting. This study aims to analyze and implement a cloud-based accounting information system in the sales cycle at PT X to enhance the effectiveness of the company’s financial management. The research methods used include observation, interviews, and documentation studies to describe the existing accounting system. The analysis results show that the current manual and semi-manual systems still cause several issues, such as delays in recording, inconsistencies in sales data, and limited real-time access to information. The implementation of a cloud-based accounting information system provides solutions through automated transaction recording, better data integration, easier access from various devices, and improved accuracy of financial reports. The findings indicate that the application of a cloud-based system in the sales cycle can improve the effectiveness of PT X’s financial management, particularly in terms of recording speed, information accuracy, and process efficiency. Therefore, this system can serve as a strategic step for the company in supporting faster and more accurate financial decision-making.